Making Sense of Sustainability: How Institutional Design Can Sustain Informal Savings and Credit Groups*. Issue 2 (June 2022) - Tan, Sarah; Savani, Manu Manthri
A majority of people in developing countries lack access to formal finance and rely on community-organised groups. These savings and credit associations (SCAs) face challenges in overcoming well-known collective action problems. SCA financial products can be understood as a common pool resource. Drawing onOstrom's (1990) design principles for self-governing local institutions, we investigate the conditions under which SCAs can achieve sustainability. Using a qualitative methodology, data were collected by examining administrative records and interviewing stakeholders from three SCAs in the Philippines. Our results indicate that adherence to the design principles is positively associated with SCA sustainability. We find that pre-existing social connections are not a necessary condition for initial adherence to the design principles but social capital may play an important role in sustainability overall. These findings contribute to our understanding of how governance design can boost the sustainability of informal groups and enhance financial inclusion among the poor.